Network unbundling and flawed coordination: Lessons from electricity and railways - Gert Brunekreeft (Jacobs University Bremen, Bremen Energy Research (BER), 2014)
What is a good balance between competition and coordination in network industries? Network unbundling aims to promote competition, but this has to be balanced against the downside of unbundling: firm-internal coordination falls away and must be replaced by external market mechanisms. This is a non-trivial task. The cost of flawed coordination as a result of fragmentation can be substantial and policy should focus more on the cost of coordination and on governance structures to secure coordination. This paper examines three persistent sources of flawed coordination: 1) a regulation versus unbundling dilemma, 2) difficulties with optimal network charging and 3) strategic behavior resulting in misaligned incentives. Practical relevance is underlined with lessons from (European) electricity and railways.
Keywords: L43; L51; L92; L94; 330; electricity; railways; unbundling; regulation; competition policy